The Rohingya crisis: Suu Kyi’s false flag and ethnic cleansing in Arakan - Hasan, Md. Mahmudul (2017)
Any discussion on the Rohingya crisis without using the term ‘genocide’ would amount to an affront to the human dignity of the Rohingya people – both the genocide casualties and survivors. Any remedy effort will remain elusive or inconclusive if the full extent of the crimes is not comprehended or recognized. It is very hard to see any immediate solution to the Rohingya crisis, as the Myanmar judicial system is completely biased against Rohingyas and the media inside Myanmar “are either lying or self-censoring.” Despite violence and mass killings of genocidal proportion for decades, not a single person is known to have been punished by the Myanmar judicial system. Moreover, the intermittent cessation of genocidal mass killings and destruction of houses and properties does not mean the ending of other forms of oppression, systematic discrimination and humiliation of the Rohingyas.